If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x(x + -1) + 3(x + -1) = 0 Reorder the terms: 2x(-1 + x) + 3(x + -1) = 0 (-1 * 2x + x * 2x) + 3(x + -1) = 0 (-2x + 2x2) + 3(x + -1) = 0 Reorder the terms: -2x + 2x2 + 3(-1 + x) = 0 -2x + 2x2 + (-1 * 3 + x * 3) = 0 -2x + 2x2 + (-3 + 3x) = 0 Reorder the terms: -3 + -2x + 3x + 2x2 = 0 Combine like terms: -2x + 3x = 1x -3 + 1x + 2x2 = 0 Solving -3 + 1x + 2x2 = 0 Solving for variable 'x'. Factor a trinomial. (-3 + -2x)(1 + -1x) = 0Subproblem 1
Set the factor '(-3 + -2x)' equal to zero and attempt to solve: Simplifying -3 + -2x = 0 Solving -3 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -2x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -2x = 0 + 3 -2x = 0 + 3 Combine like terms: 0 + 3 = 3 -2x = 3 Divide each side by '-2'. x = -1.5 Simplifying x = -1.5Subproblem 2
Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1Solution
x = {-1.5, 1}
| 28x^2+7x=0 | | 40.8/4 | | 3x-32+3x+2=180 | | s+50(6)=3s | | 2x^2+2y^2+4x-16y+26=26 | | t^2-4t=9 | | 4x+9+3x+3=180 | | j^2+6j=5 | | x+3.4=6.6 | | -12=6y+24 | | x^2+16x+37=0 | | f(x)=0.3(x^2-4x) | | 12x+2x-6y+2y-4x= | | 22=2t+2d | | 360.40-0.06(p)=p | | p^2+8p=25 | | 14-19= | | 360.40-0.06(360.40)=p | | -49-7b=-42 | | 22=2x+2y | | 8=b-1+8 | | q^2-10q-17=0 | | -2.6-11.2= | | -10+10r=80 | | -z+16z-15z+9z=-9 | | 3x-6+3x-6+2x+2+2x+2=142 | | 7x+14=42 | | (130-x)+x=130 | | -6x+x=-2-6(-12x-13) | | (20÷4*2÷5-1)/(-9(-3)-12÷3) | | x^2-43560=0 | | 17j-9j-7j=13 |